The Effect of Product Display and Promotion on Consumer Purchasing Decisions of Indomaret Ngulak Village, Sanga Village District, Musi Banyuasin Regency - Junaidi Elmanto; Siti Komariah Hildayanti; Emilda (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine whether there is an effect of product display and promotion on purchasing decisions of Indomaret consumers in Ngulak Village, Sanga Village, Musi Banyuasin Regency. This research is quantitative descriptive. The population and sample in this study were 96 people from Indomaret consumers, Ngulak Village, Sanga District, Musi Banyuasin Regency. The sampling technique uses the Accidental Sampling technique. The analysis technique used is multiple linear regression analysis, the data is processed using the help of the Statistical Product and Service Solution (SPSS) computer program version 26. The results of this study indicate that there is a positive and significant influence both partially and simultaneously between Product Display and Promotion on Decision Consumer Purchases at Indomaret, Ngulak Village, Sanga District, Village, Musi Banyuasin Regency.